The Optimizing of Prefabricated Solar Cells by Dual Plasmonic Nanoparticles (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The quest for improving the efficiency of solar cells has garnered considerable attention in numerous scientific investigations. One promising approach involves utilizing plasmons generated by metal nanoparticles to enhance the performance of photovoltaic solar cells.Materials and Methods: High-purity gold nanoparticles (AuNPs), silver nanoparticles (AgNPs), and a combination of both were synthesized using pulsed laser ablation in distilled water. Subsequently, these nanoparticles were deposited onto silicon (Si) substrates and pre-existing Si homo-junction photovoltaic cells.Results: The optical analysis of the prepared nanoparticle suspension revealed distinct plasmonic bands located at approximately 400 nm and 523 nm wavelengths for AgNPs and AuNPs, respectively. In the case of the AuNPs:AgNPs mixture, two plasmonic bands were observed, corresponding to the presence of both types of metal nanoparticles. The X-ray diffraction (XRD) analysis of the deposited nanoparticle samples on Si wafers demonstrated a polycrystalline structure for all samples. Scanning electron microscopy (SEM) imaging displayed uniformly distributed spherical Au nanoparticles on the substrate, while AgNPs exhibited some aggregations.Conclusion: The photovoltaic (PV) solar cells demonstrated an enhanced performance, attributed to the ability of the plasmonic nanoparticles to facilitate increased light absorption or enhance surface conductivity. The combination of silver and gold particles holds promise for solar surface coating, further optimizing the cells to capture a greater amount of solar radiation within their plasmon peaks. This study highlights the potential of plasmonic nanoparticles to enhance the efficiency of previously prepared PV cells.